Implementasi Program Kampus Merdeka Belajar Bagi Mahasiswa - Fitria Marisya; Despita Despita; Marsinah Marsinah; Hatidah Hatidah; RA Rodia Fitri Indriani (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The change of KKNI to the most essential independent learning campus curriculum that occurs at the elementary and middle school levels first, requires an integrative thematic learning approach, where students are invited to see, pay attention, observe the environment, and are no longer oriented to memorization. The purpose of this training is to increase the competency capacity of teachers, principals, and supervisors in understanding the implementation of the independent learning curriculum, and to improve the competence of students in the fields of knowledge, skills. This training was attended by 30 students from several universities. The results of the training show that before the training and after the training participants can understand the training material provided well, the trainees are students who are ready to take part in Merdeka Merdeka learning campus activities. It is expected that this training will be carried out for all teachers to be able to understand the implementation of the independent learning curriculum and improve the ability of teachers in the implementation of the independent learning curriculum in accordance with their respective conditions